1982
DOI: 10.1177/030006058201000302
|View full text |Cite
|
Sign up to set email alerts
|

The Subacute Effect of Bromazepam on Psychomotor Activity and Subjective Mood

Abstract: In a double-blind study, fifty-five healthy, male medical students received a tranquilizer (bromazepam, 'Lexotanil') or placebo according to dosage group (placebo, 1.5 mg and 3 mg bromazepam). The subjects were randomly allocated to three groups (placebo: n = 19; 1.5 mg: n = 19; and 3 mg: n = 17). Dependent variables tested were the subjective assessment of performance and the level of activation (self-rating), and aspects of psychomotor function were assessed using the standard testing devices. The medication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
5

Year Published

1984
1984
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 11 publications
1
4
0
5
Order By: Relevance
“…This study clearly differentiated lorazepam from clobazam by its pronounced sedative effects, especially after a single dose, and corroborated the results observed by Hindmarch & Gudgeon (1980) and Siegfried et al (1981) by disturbances of psychomotor performance 2 h after the initial dose, it caused a significant after the administration of lorazepam (Bell et clobazam, but, 1976;Saario & Seppala, 1976;Hobi et al, 1982).…”
Section: Assessment Criteria: Posturographysupporting
confidence: 89%
“…This study clearly differentiated lorazepam from clobazam by its pronounced sedative effects, especially after a single dose, and corroborated the results observed by Hindmarch & Gudgeon (1980) and Siegfried et al (1981) by disturbances of psychomotor performance 2 h after the initial dose, it caused a significant after the administration of lorazepam (Bell et clobazam, but, 1976;Saario & Seppala, 1976;Hobi et al, 1982).…”
Section: Assessment Criteria: Posturographysupporting
confidence: 89%
“…However, a longer motor reaction time was observed 6 hours after bromazepam ingestion 7 . In another study, Hobi et al observed a lengthening of reaction time for all three groups (placebo, bromazepam 1.5mg and bromazepam 3mg), but concluded that this result was due to the type of experimental design used, and only slightly to the drug's action 22 .…”
Section: Discussionmentioning
confidence: 98%
“…Quanto aos testes de atenção e alerta, ocorreram melhoras significativas nos três grupos (em função da aprendizagem). Isso sugere que em doses relativamente baixas, o Bromazepam não é capaz de influenciar substancialmente tais variáveis 6 , hipó-tese confirmada por dados pilotos de nosso laboratório. Investigações envolvendo vários benzodiazepínicos (alprazolam, bromazepam, diazepam e lorazepam) apontam diferentes resultados em função da dosagem e tempo de tratamento 27 .…”
Section: Discussionunclassified
“…O Bromazepam, derivado benzodiazepínico tem a seguinte designação: 7-bromo-1, 3-dihydro -5-(2-pyridyl)-2H-1, 4-benzodiazepínico-2. Tem sido amplamente utilizado na Psiquiatria há cerca de 4 décadas para tratamento dos transtornos de ansiedade por apresentar propriedades ansiolítica, anticonvulsiva, miorelaxante e hipnótica em caso de dose elevada [6][7][8] . Os efeitos ansiolítico, analgésico e hipnótico do Bromazepam são exercidos pela intensificação da neurotransmissão mediada pelo GABA.…”
unclassified